Influence of operating temperature on the activation efficiency of Li-ion cells with xLi2MnO3-(1-x)LiMn0.5Ni0.5O2 electrodes - Nazario-Naveda, Renny (2022)
In this study, the effect of operating temperature at 55 °C on xLi2MnO3-(1-x)LiMn0.5Ni0.5O2 electrodes during the charge/discharge process at different current densities was investigated. X-ray diffraction (XRD) and scanning electron microscopy (SEM) were used for structural and morphological analysis of the fabricated cathode materials, while charge-discharge curves and differential capacity were used to study the electrochemical behavior. Results confirm the formation of the structures with two phases associated withthe components of the layered material. It was found that at 55 °C, a capacity higher than 357 mAh g-1 could be achieved at a voltage of 2.5-4.8 V vs. Li/Li+, which was larger than the capacity achieved at room temperature. At 55 °C, a change in valence could be observed during charging and discharging due to the change in the position of the peaks associated with Mn and Ni, highlighting cathodic material with x = 0.5 as the material that retains the layered structure at this temperature. This work confirms the good performance of electrodes made with this material at elevated temperatures and gives a better understanding of its electrochemical behavior.